ANALISIS PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DAN MINAT BELI ULANG SMARTPHONE MEREK XIAOMI PADA MASA PEMBELAJARAN JARAK JAUH - Fatana Suastrini; Muhammad Helmy Reza (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The Covid-19 pandemic has made the world of education change the way in the learning process. The need for a communication device, in this case a smartphone, has become a necessity. This study aims to determine the effect of price and product quality on purchasing decisions and intention to repurchase Xiaomi brand smartphones during the distance learning period. The type of research used is quantitative research. The location of the research was carried out at the Mataram State Islamic University. The sample used in this study were students totaling 100 people. The analytical technique used in this research is descriptive analysis, data analysis, and statistical analysis with SEM (Structural Equation Modeling). The results of this study indicate that the price and quality of the product affect the purchasing decisions and interest in repurchasing Xiaomi brand smartphones in students.